Urinary Morbidity in Men Treated With Stereotactic Body Radiation Therapy (SBRT) for Localized Prostate Cancer Following Transurethral Resection of the Prostate (TURP) - Pepin, Abigail; Aghdam, Nima; Shah, Sarthak; Kataria, Shaan; Tsou, Harry; Datta, Subhradeep; Danner, Malika; Ayoob, Marilyn; Yung, Thomas; Lei, Siyuan; Gurka, Marie; Collins, Brian T.; et al. (Frontiers in Oncology, 2020)
Stereotactic body radiation therapy (SBRT) provides similar clinical outcomes as other radiation modalities for prostate cancer. Data reporting on the safety of SBRT after TURP is limited. Herein, we report our experience using SBRT to deliver hypofractionated radiotherapy in patients with a history of TURP including physician-reported toxicities and patient-reported quality of life. Forty-seven patients treated with SBRT from 2007 to 2016 at Georgetown University Hospital for localized prostate carcinoma with a history of prior TURP were included in this retrospective analysis. Treatment was delivered using the CyberKnife® (Accuray Incorporated, Sunnyvale, CA) with doses of 35 Gy or 36.25 Gy in 5 fractions without prostatic urethral sparing. Toxicities were recorded and scored using the CTCAE v.4. Cystoscopy findings were retrospectively reviewed. Urinary quality of life data was assessed using the International Prostate Symptom Scoring (IPSS) and Expanded Prostate Cancer Index Composite 26 (EPIC-26). A Wilcoxon signed-rank sum test was used to determine if there was a statistically significant increase or decrease in IPSS or EPIC scores between timepoints. Minimally important differences were calculated by obtaining half the standard deviation at start of treatment. Forty-seven patients at a median age of 72 years (range 63-84) received SBRT. The mean follow-up was 4.7 years (range 2-10 years). Late Grade 2 and grade 3 urinary toxicity occurred in 23 (48.9%) and 3 (6.4%) men, respectively. There were no Grade 4 or 5 toxicities. Approximately 51% of patients experienced hematuria following treatment. Mean time to hematuria was 10.5 months. Twenty-five cystoscopies were performed during follow-up and the most common finding was hyperemia, varices of the bladder neck/TURP defect, and/or necrotic tissue in the TURP defect. Baseline urinary QOL composite scores were low, but did not clinically significantly decline in the first two years following treatment. In patients with prior TURP, prostate SBRT was well tolerated. GU toxicity rates were comparable to similar patients treated with conventionally fractionated radiation therapy. Urinary quality of life was poor at baseline, but did not worsen clinically over time. Stricter dosimetric criteria could potentially improve the rate of high-grade late toxicity, but may increase the risk of peri-urethral recurrence.